MiR-429 Inhibits the Angiogenesis of Human Brain Microvascular Endothelial Cells through SNAI2-Mediated GSK-3β/β-Catenin Pathway. (20th December 2021) - Sun, Yameng; Ding, Shenghao; Fan, Yiling; Shen, Fei; Dong, Qing; Zhao, Bing; Pan, Yaohua; Wan, Jieqing
Abstract : MicroRNA (miRNA) dysfunction has been confirmed as a key event of ischemic stroke appearance. This study is aimed at revealing the role of miR-429 in the angiogenesis of HBMECs. The HBMECs were treated with oxygen and glucose deprivation (OGD) to establish the ischemic cell model. The qRT-PCR was used to measure the expression levels of the miR-429 in the serums of the patients or cells, and CCK-8, wound healing assay, and tube formation assay were used to observe the effects of miR-429 on the phenotype of HBMECs. Moreover, the Targetscan, dual-luciferase reporter assay, and Western blot were used to reveal the downstream target and regulation mechanism of miR-429 in OGD-induced HBMECs. The results showed that miR-429 was significantly upregulated in the serums of the patients, and overexpressed miR-429 could extremely inhibit the viability, migration, and tube formation of OGD-induced HBMECs. Furthermore, it was found that SNAI2 was a downstream factor of miR-429, and SNAI2 could rescue the effects of miR-429 on OGD-induced HBMECs. Besides, the Western blot showed that miR-429 could affect the activity of GSK-3 β / β -catenin pathway via inhibiting the expression of SNAI2. In conclusion, this study suggests that miR-429 inhibits the angiogenesis of HBMECs through SNAI2-mediated GSK-3 β / β -catenin pathway.